2013
DOI: 10.1016/j.neuchi.2012.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar spinal stenosis: Which predictive factors of favorable functional results after decompressive laminectomy?

Abstract: The long-term results of surgical treatment of lumbar spinal stenosis were moderate with an improved outcome in 49.5% of cases in our study. The only independent factor to a favorable outcome was the low comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 28 publications
0
39
1
2
Order By: Relevance
“…[1][2][3] Specific clinical outcome of spine surgery with fusion for degenerative lumbar spine conditions in 208 patients showed 62.5% satisfied, 19.7% partially satisfied, and 17.8% of patients dissatisfied. 4 Postsurgical continued pain (PSCP) sends patients to the offices of physicians, surgeons, and pain specialists alike in overwhelming numbers.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Specific clinical outcome of spine surgery with fusion for degenerative lumbar spine conditions in 208 patients showed 62.5% satisfied, 19.7% partially satisfied, and 17.8% of patients dissatisfied. 4 Postsurgical continued pain (PSCP) sends patients to the offices of physicians, surgeons, and pain specialists alike in overwhelming numbers.…”
Section: Introductionmentioning
confidence: 99%
“…5,11 In this study, we aimed to determine the specific preoperative prognostic factors associated with risk for reoperation in patients who have undergone a lumbar laminectomy. Smoking as an independent predictor of reoperation after lumbar laminectomy: a study of 500 cases obJect This study aimed to identify the factors predicting an increased risk for reoperation in patients who had undergone a lumbar laminectomy.…”
mentioning
confidence: 99%
“…Other studies have similarly reported worse results following LBS in the presence of comorbidities affecting walking ability . In a prospective study of 98 patients operated with decompressive lumbar laminectomy for spinal stenosis, Foulongne et al demonstrated that low Charlson comorbidity index scores was the strongest predictor of favorable functional outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…There are several studies reporting worse outcomes following LBS if there is a preoperative disorder affecting the patients walking capacity, such as hip osteoarthritis . Conversely, absence of comorbidities (as measured by Charlson comorbidity index) and mobility disorders positively influence the outcomes of LBS …”
mentioning
confidence: 99%